PENGARUH AKUNTABILITAS, KOMPETENSI DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS HASIL AUDIT - Herlina Herlina; Murhaban Murhaban (LPPM STIE Lhokseumawe, 2019)
This study aims to test the Influence of Accountability, Competence And Auditor Independence of Quality of Audit Results (Case Study At Lhokseumawe City Inspectorate). The data used in this study is the primary data as much as 32 samples with purposive sampling technique. The method used to analyze between independent variables with dependent variable is multiple linear regression method and test of classical assumption. Result of research of accountability variable, competence and independency of auditor simultant have a significant effect to quality of audit result at Inspectorate of Lhokseumawe city. While the results of partial research accountability variables do not affect the quality of audit results, competenc variables do not affect the quality of audit results and auditor independence variables have a significant effect on the quality of audit results at Inspectorate Kota Lhokseumawe.